2016
DOI: 10.1186/s13071-016-1385-9
|View full text |Cite
|
Sign up to set email alerts
|

Mating competitiveness of sterile genetic sexing strain males (GAMA) under laboratory and semi-field conditions: Steps towards the use of the Sterile Insect Technique to control the major malaria vector Anopheles arabiensis in South Africa

Abstract: BackgroundAnopheles arabiensis Patton is primarily responsible for malaria transmission in South Africa after successful suppression of other major vector species using indoor spraying of residual insecticides. Control of An. arabiensis using current insecticide based approaches is proving difficult owing to the development of insecticide resistance, and variable feeding and resting behaviours. The use of the sterile insect technique as an area-wide integrated pest management system to supplement the control o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 34 publications
1
37
0
1
Order By: Relevance
“…Identification of females and males in a pest species can give great value to the development of new control methods and understanding, for example, the seasonal pattern of oviposition might be important for pest control. Sex‐specific control methods, are well known, for example, sterile insects in malaria control (Munhenga et al ., ) or pheromone traps for lepidopteran pests (Megido et al ., ), which minimize the mating success. Sex‐linked insecticide resistance is known from the housefly and Colorado potato beetle (Hawthorne, ; Rinkevich et al ., ; Hojland et al ., ), but is more the exception than the rule in insecticide resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of females and males in a pest species can give great value to the development of new control methods and understanding, for example, the seasonal pattern of oviposition might be important for pest control. Sex‐specific control methods, are well known, for example, sterile insects in malaria control (Munhenga et al ., ) or pheromone traps for lepidopteran pests (Megido et al ., ), which minimize the mating success. Sex‐linked insecticide resistance is known from the housefly and Colorado potato beetle (Hawthorne, ; Rinkevich et al ., ; Hojland et al ., ), but is more the exception than the rule in insecticide resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Mating competitiveness experiments showed that irradiated male mosquitoes are fertile as wild counterparts under semi-field conditions. However, they were not as competitive under laboratory conditions [14]. …”
Section: Discussionmentioning
confidence: 99%
“…Broadly speaking, comparisons of the genetics of colony populations and field populations is important particularly in genetic control trials because population genetic make-up can affect physiological and behavioural fitness traits, and hence the efficacy of the genetic control methods [810]. The fitness of Anopheles arabiensis male populations in SIT trials in northern and south Africa, showed that prolonged colonization, irradiation, and transportation do not impede mating vigour and competitiveness of male mosquitoes [1114]. Colonization of An.…”
Section: Introductionmentioning
confidence: 99%
“…Two local A. arabiensis laboratory strains were used to develop the GSS strain. The first strain (GAMA) was developed by the introgression of the Sudanese A. arabiensis GSS ANO IPCL1 males (carrying the dieldrin resistance rdl gene on the Y chromosome) with A. arabiensis females colonized from material collected in 2010 from the Kruger National Park (Munhenga et al ., ). The GAMA strain had not been purified for the rdl gene for a number of generations prior to this study.…”
Section: Methodsmentioning
confidence: 97%
“…Over the past 6 years, extensive baseline studies on the population dynamics of wild target A. arabiensis populations have been carried out in the Kruger National Park and northern KZN, culminating in the identification of a pilot release site (Munhenga et al ., , ). In addition, mating competitiveness of representative laboratory strains has been established (Munhenga et al ., ). Apart from this baseline information, there are other aspects of the SIT programme that require optimization before pilot releases can be done.…”
Section: Introductionmentioning
confidence: 97%